The Urgency Of Trademark Protection For A Musician Name - AL.SENTOTSUDARWANTO, (The journal of contemporary issues in business and government, 2021)
This article traces the urgency of trademark protection for a musician name. The result of the discussion shows that people may deceived if new musicians hitch a ride on the name of famous musicians to perform their songs or any other form of artistic works on a concert or performance. Similarities on the name may lead to reputation damage or goodwill of the previous musician. Every person or group intends to use the names of existing name of a musician in productions other than songs or albums and performances shall obtain permission from the concerned musician to receive benefit sharing on the utilization of the name as a means to prevent adverse conducts of unauthorized party. Such measures are aimed to conduct production and trading services in the form of entertainment services as classified in class 41 of the Nice Agreement. The process of registering the name of a musician is generally equivalent with trademark registration stipulated in the Law Number 15 of 2001 concerning Trademark